RESTORATIVE JUSTICE: PARADIGMA BARU PERADILAN PIDANA - Satria, Hariman (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2018)
Direction of criminal justice in Indonesia is currently experiencing a shift from retributive to restorative-rehabilitative or daad-dader-strafrecht or model of balance of interests. This is confirmed by Laws No. 11 of 2012 on Juvenile Justice System, which states in Article 6 to Article 8 that emphasizes the concept of restorative justice through diversion. Both of these concepts allow the settlement of children out of the criminal justice. However, not all criminal offenses committed by children can be settled out of court (diversion) unless two conditions are met: imprisonment for a criminal offense under seven years and is not a repetition of criminal offenses (recidivism). The essences of restorative justice are: First, in the settlement of children, it is necessary that the offenders and their families and victims and their families can sit together to discuss the settlement of issues including reparations to victims (restitution in integrum). Second, the essence of restorative justice is to give punishment to the offenders but the punishment is didactic, in order to benefit to both of the perpetrator and the victims.Â This is in line with an adagio â€œdelinquens per iram provocatus puniri debet mitiusâ€. Third, regulation of a quo using two approaches: i.e. victims and offenders mediation approaches as implemented in North America as well as approach that emphasizes restitution and reparation (court based restitutive and reparative measure), as practiced in the United Kingdom